Interpersonal Competence, Work Environment, and Work Discipline as Predictors of Teachers’ Job Satisfaction: The Mediating Role of Intrapersonal Competence among Junior High School Teachers in Indonesia - Pitriyani, Pitriyani; Firman, Firman; Rosmiati, Rosmiati; Wulandari, Bunga Ayu (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
This study examines the effects of interpersonal competence, work environment, and work discipline on teachers’ job satisfaction, with intrapersonal competence as a mediating variable, among 285 junior high school teachers in Muaro Jambi, Indonesia. A quantitative cross-sectional survey design was applied, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that work discipline (β = 0.336, p < 0.001), interpersonal competence (β = 0.430, p < 0.001), and work environment (β = 0.357, p < 0.001) have significant direct effects on job satisfaction. Intrapersonal competence also significantly affects job satisfaction (β = 0.241, p = 0.001) and mediates the relationships between work discipline (indirect β = 0.147, p = 0.001), interpersonal competence (indirect β = 0.115, p = 0.001), and work environment (indirect β = 0.106, p = 0.001). The model explains 88.2% of the variance in intrapersonal competence (R² = 0.882) and 83.0% of the variance in job satisfaction (R² = 0.830). These findings demonstrate that teachers’ job satisfaction is shaped not only by organizational conditions but also by intrapersonal competence. The study contributes theoretically by clarifying the mediating role of intrapersonal competence as a mechanism linking organizational and personal factors. The novelty lies in empirically combining three organizational predictors with intrapersonal mediation in the Indonesian junior high school context. Practical implications include enhancing workplace conditions, strengthening work discipline, and supporting teachers’ intrapersonal development. A limitation is the cross-sectional design, which does not permit causal conclusions.